ONLY STATE PRESIDENT? - MARIUS VACARELU (Challenges of the Knowledge Society)
Last 4 years showed to Romania that is impossible to deny the national feeling of passionately activism in politics: for sure, we are Latin and we remain Latin. All this big debate was related to a person and to his position in Romanian state. However, no one was able to be totally independent in his/her analyze, and, if he/she was totally independent, the press take hundreds of attacks against every person who wrote any opinion in this special problem: what kind on republic want we? Politicians want to change this year our Constitution, but I believe they won't be able to do this. In this context, we must start a real national debate of public law specialists, about this institutional problem: we want one president and one prime-minister with powers, or a prime-minister with powers and a president like a puppet? This kind of speech appears now because in 2012 and the key-word of our politics was the legitimacy. In this case, when this political concept become too strong, it is necessary to offer a legal answer. Our text tries to be one of them.